Do Male Desert Gobies Compromise Offspring Care to Attract Additional Mating Opportunities? - Symons, Nicholas (Public Library of Science, 2011)
Males often play a critical role in offspring care but the time and energy invested in looking after young can potentially limit their ability to seek out additional mating opportunities. Recent studies, however, suggest that a conflict between male parental effort and mating effort may not always be inevitable, especially if breeding occurs near the nest, or if parental behaviours are under sexual selection. Accordingly, we set out to experimentally investigate male care and courtship in the desert goby Chlamydogobius eremius, a nest-guarding fish with exclusive paternal care. Despite courtship occurring near the nest, we found that when egg-tending males were given the opportunity to attract additional females, they fanned their eggs less often, engaged in shorter fanning bouts, and spent more of their time outside their nests courting. Our findings highlight the importance of understanding the circumstances under which reproductive tradeoffs are expected to occur and how these, in turn, operate to influence male reproductive decisions.